Pemberian Nafkah terhadap Anak Dari Perkawinan Tidak Tercatat Menurut UU Perkawinan dan KHI - Syaddan Dintara Lubis (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
At this time there were many husband and wife couples who took the path of carrying out unregistered marriages, this marriage was a marriage that was not registered in the country which was really carried out by the general public in Indonesia, seen in Islamic law it was permissible to carry out unregistered marriages but in strict regulations in force in the country of Indonesia does not recognize that this marriage is a legal marriage because this marriage is not registered in the country, in the family it cannot be separated from conflict between husband and wife resulting in quarrels that can lead to divorce this conflict is a situation that is definitely not wanted by children , based on the data found that according to the provisions of Article 27 Perkap No. 9 of 2010 stipulates that the husband's obligation to provide maintenance to his wife and children after a divorce, is determined in accordance with a court decision that has permanent legal force, in the compilation of Islamic law in Surah Al-Baqarah verse 233 firmly says that a father's obligation to provide for his child even as a child category. In this journal research the authors use the normative-empirical legal method by combining elements of normative law which are then supported by empirical data. After a divorce occurs, it is inseparable from the obligation of a husband or wife to provide for children from the results of a husband and wife in the context of compilation of Islamic law, parents have the obligation to provide for their children from marriage, but in Law No. 1 of 1974 concerning marriage, article 43 means that there is no the obligation for the husband to provide for his child if the marriage is not registered according to the applicable law is all left to the wife. Keywords: Children's livelihood, KHI, UU Marriage